The Influence of Green Banking and Green Accounting on Profitability of Banks Listed on the Indonesia Stock Exchange - Nada Fadilla; Lilik Handajani; Ayudia Sokarina (International Journal of Management, Accounting and Economics)
This study examines the influence of green banking and green accounting on the profitability of banks listed on the Indonesia Stock Exchange (IDX) from 2018 to 2022. Using secondary data obtained from the annual and sustainability reports of 30 selected banks, hypothesis testing was performed through panel data regression analysis with EViews 13 software. The results demonstrate that both green banking and green accounting have a significant positive effect on profitability. Green banking practices, such as sustainable financing and operational efficiency measures, contribute to reduced operational costs and attract investors and customers (p-value = 0.0044). Similarly, green accounting, which integrates environmental considerations into financial reporting, enhances transparency, reduce risks, and improve a bank’s public image (p-value = 0.0003). These findings highlight that the adoption green banking and green accounting not only supports environmental sustainability but also leads to improved financial performance. This research suggests that Indonesian banks should embrace these practices to ensure long-term profitability while aligning with global sustainability trends.